The Sage handbook of contemporary cross-cultural management - Szkudlarek, Betina; Romani, Laurence, 1972-; Caprar, Dan V.; Osland, Joyce, 1949- (Sage reference, 2020)
This Handbook presents a comprehensive and contemporary compendium of the field of cross-cultural management (CCM). In recognition of current trends regarding migration, political ethnocentrisms and increasing nationalism, the chapters in this volume not only cover the traditional domains of CCM such as expatriation, global (virtual) teamwork and leadership, but also examine emerging topics such as bi/multi-culturalism, migration, religion and more, all considered from a global perspective. The result is a Handbook that acknowledges and builds on a variety of research traditions (from mainstream to critical), updates existing knowledge in relation to current challenges, and sets the direction for future research and developments, making this an invaluable resource for researchers in the field, and across related areas of international business, management, and intercultural relations.